ADSORPSI ZAT WARNA RHODAMINE B MENGGUNAKAN SERBUK KULIT BUAH LAI (Durio kutejensis (Hassk.) Becc.) SEBAGAI ADSORBEN - Sam, Risna Fitriani; Wirawan, Teguh; Aziz, Abdul (Jurusan Kimia FMIPA UNMUL, 2024)
Rhodamine B dye, which is widely used in the textile industry, has the potential to reduce environmental quality because it is difficult to decompose and makes it a toxic substance. Therefore, textile industry waste must be processed first before being released into the environment, for example through an adsorption process. In this research, the adsorbent was made from Lai fruit peel powder and the optimum conditions and performance of the adsorbent were determined based on the optimum pH, optimum time, adsorption capacity, type of isotherm (Langmuir or Freundlich), and adsorption thermodynamics. The adsorbent was made by washing the lai fruit peel powder repeatedly using boiling distilled water until the filtrate was colorless, then heating, crushing and sifting with a 60 mesh sieve. Lai fruit peel powder was chemically activated by soaking in 2 M HCl solution for 24 hours. The FT-IR spectrum of Lai fruit peel powder shows the presence of C-O, C=C, C-H, and O-H stretching vibration groups. Based on Scanning Electron Microscopy (SEM), activated lai fruit peel powder shows more open pores. The absorption value was determined using a UV-Vis spectrophotometer. The optimum conditions for adsorption of rhodamine B dye occur at pH 5, contact time 75 minutes, maximum adsorption capacity of 118.5422 mg/g following the Freundlich isotherm adsorption pattern and adsorption occurs physically.